The conception of dialectal point in the dialectal database Tarmynas - Mikulėnienė, Danguolė; Čepaitienė, Agnė (Baltistica, 2021)
The article describes the shift in the conception of dialectal points, highlighting the path taken by the developers of the model of the Database of the Lithuanian Local Language Variants, or Tarmynas, for points of the Atlas of the Lithuanian Language (ALL) to become the Tarmynas points. With the help of GIS tools, the ALL points in the Tarmynas are construed as Thiessen polygons. Based on the Thiessen polygon approach, the Tarmynas has preserved the conception of points and point network present in the ALL, which resembles the network of points designed by Antanas Salys back in the mid-20th century quite closely. The GIS tools that are applied in the Tarmynas in an all-encompassing manner allow making an objective assessment of the viability of points, which can provide a statistically reliable backbone for predicting the shift in local language variants.